STUDI KASUS PENERAPAN TEKNIK AFIRMASI TERHADAP TINGKAT STRES KERJA PERAWAT DI RUANG RAWAT INAP TULIP RUMAH SAKIT BHAYANGKARA TK.I R. SAID SUKANTO - Sarah Nurul Izzah Mustofa (2022)
One of the problems that often arise in hospitals, especially nurses, is the work stress of nurses. Work stress is often experienced because the workload is too high. Based on the data found by the author that there are 5 nurses out of 10 nurses in the Tulip Room of Bhayangkara Hospital TK.I R.Said Sukanto experiencing work stress. Therefore, the authors carry out work stress management using affirmation techniques to nurses. The stages of this case study start from giving a job stress questionnaire as a pre test before being given affirmation therapy using the Occupational Stress Inventory-Revised Edition (OSI-R) Job Stress Measurement Questionnaire, after that the author gives or implements affirmation techniques to nurses who experience work stress. . Affirmation therapy was given for 3 days with a duration of 15 minutes each session and was carried out in a quiet room. After being conducted for three days in a row, the researcher conducted a post test using the same questionnaire to describe the effectiveness of the affirmation technique on work stress experienced by nurses. post test results show that there is a decrease in work stress on nurses who are given affirmation techniques. Affirmation techniques are highly recommended for health workers, especially nurses to deal with work stress that occurs in hospitals so that nurses can manage work stress appropriately and effectively. Keywords : Affirmation Technique, Nurse, Work Stress